Os herdeiros do lixão do Roger: contribuições escolares para a relação aluno e pertencimento social - Silva, Sheylene Tathiana Lages da (2021)
This study aims to point out the favoritism of the construction of social identities through the Brazilian educational process, focusing specifically on subjects belonging to communities located in the peripheries of urban centers. This dissertation is a study on the community of Roger's Neighborhood. This social group belongs to the neighborhood that housed for decades (1958-2003) the largest open-air dump in the city of João Pessoa, State of Paraíba. The general objective of this research is: to analyze the school contributions related to the recognition of the social belonging of children and adolescent’s heirs of the former Dump of Roger. The specific objectives are: to understand if there are school contributions for the children and adolescents of Roger's Neighborhood to be positively related to their social belonging. We sought to collaborate to the perception of the socioeconomic obstacles faced by local residents, relevant to their historicity, regionality and belonging. It also sought to identify cultural and artistic expressions that contribute in parallel with the social education of children and adolescents in this place. In addition, it was intended to understand how educational public policies are contributing, in a public context, as basic contributions to actions that welcome and respect the community specificities of this target audience. Methodologically, this is a qualitative, documentary research with the application of interview and questionnaire. The population sampling delimited for this study comprised a number of 35 participants, 27 parents and/or guardians of the students, and 08 teachers who worked in a neighborhood school. The data were analyzed from the perspective of historical and dialectical materialism. The results of this investigation prove that there is an educational process and that this has been a community claim. Therefore, in neoconservative times the need to develop this research shows that investments need to be intensified in order for students to have access to better education.